Cantilever-based biaxial FBG inclinometer with low cross-axis sensitivity - Ramalingam, Nimalrajh; Yang, Hangting; Lim, Kok-Sing; Ahmad, Harith (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
This work proposes and demonstrates a biaxial sensing inclinometer based on two FBGs surface-mounted on two separate thin cantilevers with a diminishable cross-axis sensitivity. The measured sensitivities for the inclination angles in the x-z plane and y-z plane are 34.87 and 33.49 pm/deg, respectively. To enhance the protection of the delicate FBGs and minimize axis-to-axis cross-sensitivity, the carbon-steel cantilevers are strategically arranged in a perpendicular configuration, resulting in an impressively low cross-sensitivity value of just 0.9275%. This alignment not only offers mechanical shielding but also ensures optimal performance and accuracy for the FBGs.
Optica Applicata, Vol. 54, 2024, nr 2, s. 189-203
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; inclinometer; cantilever; cross-sensitivity; fiber Bragg grating